Exercise-induced dehydration causes malabsorption of carbohydrate rich pre-exercise meal - Huschtscha, Z.; Russo, I.; Snipe, R. M. J.; Dixon, D.; Camões-Costa, V.; Costa, R. J. S. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
It is well established that endurance exercise stress compromises gastrointestinal integrity and functional responses, potentially leading to performance debilitating gastrointestinal symptoms (GIS). However, the magnitude to which exercise-induced dehydration impact gastrointestinal integrity and functional markers is less known. The study aimed to determine the impact of exercise-induced dehydration on gastrointestinal integrity and functional responses, and GIS.